Quality of Administration Courses and Higher Education Institutions in Joinville - SC: a study on factors related to job market awareness of students - Mainardes, Emerson Wagner; Domingues, Maria José Carvalho de Souza (Review of Business Management, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> In a market of competitive higher education as it is the case of Brazil, to possess a quality image has been fundamental to attract and to keep students in a Higher Education Institution (HEI). This study aimed to determine the quality of administration courses and of HEIs that are offered in Joinville, SC, as for aspects related to the job market. For the accomplishment of the study, studies that treat of the quality in educational organizations, meeting 6 attributes that measure the quality of a course and of a HEI as for factors related to the job market were searched. Afterwards, it was conducted a quantitative-descriptive research close to the graduates in two of five HEI that offer the graduation in administration in Joinville, SC. A questionnaire was applied structured not disguised, with closed questions to 292 graduates of these two HEIs. With the collected data, these graduates were characterized and were identified the attributes of better and worse performances as the quality of these courses and HEIs only considering linked attributes to the job market. We have also found the attributes that most contribute to the perception of quality of a course and of an institution in the students’ vision, when related to factor linked to the job market. The courses and HEIs have been well evaluated in terms of quality for the labor market, and the reputation of the courses and of HEIs is the attribute of better performance according to the students. Key words: Higher education institutions. Universities. Quality in educational organizations. Graduation in administration. Job market.